KINERJA DINAS PEKERJAAN UMUM DALAM PEMELIHARAAN JALAN DAN JEMBATAN DI KABUPATEN TOBA SAMOSIR - Elisabet, Megaria; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The condition of road and bridge should ensure the movement of human and tool smoothly, safely, quickly and comfortably. That is why it should be free from any damage. Department of Public Work of Toba Samosir Regency as one of the agenciyes which handles maintenance of road and bridge generally does not have good performance yet. Unavailable human resources, unsupported tools and infrastructures, community view and natural condition are same barrier that usually found. The problem in this study is hoe Department of Public Work performance of Toba Samosir Regency in gaining its purpose that is to handle the maintenance of road and bridge and factors that affect the organizational performance.The purpose of this study is to know the performance Department of Public Work of Toba Samosir Regency from 2010-2014 to handle the maintenance road and bridge and to know factors that affect the performance Department of Public Work to handle maintenance road and bridge.This study used quality research methodsto the study og descriptive data. The researcher used interview techniques, observation and documentation specified by purposive random sampling technique to collecting the data.From the analysis of the qualitative descriptive data that Department of Public Work Performance to handle maintenance road and bridge categorized yet good, the thing which seen from conceited the road and bridge damage.Keywords : performance, maintenance of road and bridge